Studi Komparasi Hadis dan Sunnah Dalam Perspektif Fazlur Rahman - Desriliwa Ade Mela; Dasril Davidra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
This study is based on the premise that rapid social change has enabled people in the field of Qur'an and Hadith research methods to further develop and follow developments in ways of expressing new ideas in the field of Sunnah and/or Hadith. I am motivated because of me. and time changes. One of the Muslim scholars who studied the methodology of interpreting the Qur'an is Fazlur Rahman. Fazlur Rahman's thoughts in the field of hadith were motivated by his response to the sunnah and hadith controversies in Pakistan. The purpose of this study is to explain Fazlur Rahman's thoughts on Sunnah and Hadith. This research methodology uses literature search. Data from various literature documents, articles and books. The results of this study indicate that Fazra Rahman's thinking is driven by the emergence of the Muslim status quo, which tends to close the door of Ijihad, ultimately leading to extraordinary intellectual stagnation, and people's fear of change in the world. This means that they no longer pay attention to development. Give them time to react. Closing the door of ijtihad has a logical consequence of opening the door of taklid. Many orientalists also have misconceptions about the sunnah. In this case, Rahman's approach in interpreting the legal tradition is a historical-sociological approach. From here, Rahman developed several ideas to examine the methodology of hadith studies. This includes a historical sociological approach. This allows us to create new, dynamic and creative nuances for the gradual realization of the moral message of the Sunnah of the Prophet. To keep up with the times. Through such an approach, hadith is expected to be a gateway for the dynamics of the formation of Islamic law.